2021
DOI: 10.3389/fpls.2021.703020
|View full text |Cite
|
Sign up to set email alerts
|

Production of Human Acid-Alpha Glucosidase With a Paucimannose Structure by Glycoengineered Arabidopsis Cell Culture

Abstract: Plant cell cultures have emerged as a promising platform for the production of biopharmaceutics due to their cost-effectiveness, safety, ability to control the cultivation, and secrete products into culture medium. However, the use of this platform is hindered by the generation of plant-specific N-glycans, the inability to produce essential N-glycans for cellular delivery of biopharmaceutics, and low productivity. In this study, an alternative acid-alpha glucosidase (GAA) for enzyme replacement therapy of Pomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…However, the use of this platform is hindered by the generation of plant-specific N -glycans, the inability to produce essential N -glycans for cellular delivery of biopharmaceutics and low productivity. Sariyatun et al ( 117 ) producted a hGAA for ERT with a paucimannose structure-Man3GlcNAc2 (M3), without the plant-specific N -glycans by glycoengineered in Arabidopsis alg3 cell culture.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of this platform is hindered by the generation of plant-specific N -glycans, the inability to produce essential N -glycans for cellular delivery of biopharmaceutics and low productivity. Sariyatun et al ( 117 ) producted a hGAA for ERT with a paucimannose structure-Man3GlcNAc2 (M3), without the plant-specific N -glycans by glycoengineered in Arabidopsis alg3 cell culture.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some mammal native SPs can also be recognized and accurately processed in plant cells. For instance, the native SP of human growth hormone (hGH) led to the correct processing and apoplast targeting of active hGH in N. benthamiana [88], and the native human acid-alpha glucosidase (GAA) SP was shown to be fully capable of facilitating the entrance of GAA into the ER lumen, leading to the eventual secretion into the Arabidopsis cell culture medium [89]. The native murine mAb24 heavy chain-derived signal peptide (LPH) was also frequently used for the expression of viral glycoproteins [90].…”
Section: Apoplastmentioning
confidence: 99%
“…Previous results have shown that the Arabidopsis HEXO mutant and N. benthamiana HEXO RNAi knockout line effectively prevent the formation of the paucimannosidic MMXF N-glycan [281,282]. However, the paucimannosidic structure MM (Man 3 GlcNAc 2 or M3) has been reported to be indispensable and superior in mannose receptor (MR)-mediated cellular delivery of biopharmaceutics because of its high MR-binding efficiency and relatively low clearance rate [89]. Carrot suspension cell-produced Elelyso (i.e., recombinant human β-glucocerebrosidase) is an example of a recombinant protein with the paucimannosidic type N-glycan [131].…”
Section: Elimination Of Plant Specific N-glycan Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the secretion mechanisms, which are highly conserved among eukaryotes, allow SPs of a heterologous origin—for example, animal SPs in a plant expression system—to be employed for targeting recombinant proteins to the apoplast. In particular, the authentic SP of human growth hormone ensures the correct processing and translocation of human growth hormone to the apoplast of N. benthamiana [ 16 , 119 ], as does the authentic SP of human acid α-glucosidase in A. thaliana cell culture [ 120 ]. Various SPs yield different secretion efficiency levels; hence, these peptides should be individually selected for each expression system.…”
Section: Intracellular Transport Of Proteins To the Er And Its Deriva...mentioning
confidence: 99%